Relationship between workload and nurses response time in the emergency room: A literature review - Kusuma, M Iqbal Angga; Palupi, Eva Riantika Ratna; Wirawan, Nandar (STIKes Al-Ma'arif Baturaja, 2025)
Background The Emergency Department (ED) is a critical hospital unit that requires nurses to provide fast and accurate responses to life-threatening conditions. Nurse response time is a key quality indicator, yet delays often occur due to excessive workload. Studies suggest that high workload negatively affects response time, but a comprehensive review in the Indonesian context remains limited. Objective This study aimed to critically review existing literature on the relationship between nurses’ workload and response time in emergency care settings in Indonesia. Methods A systematic literature review was conducted using Google Scholar and PubMed databases. Articles published between 2019 and 2025 were screened based on inclusion criteria: studies conducted in Indonesian EDs, discussing both workload and response time, available in full-text, and written in English or Indonesian. Quality appraisal was performed using the JBI Critical Appraisal Tools, resulting in 8 eligible articles out of 360 initially identified. Results Most of the reviewed studies found a significant relationship between high workload and delayed nurse response time. Nurses with lower workload were more likely to meet the ≤5-minute standard. Other influencing factors included training, years of experience, facility infrastructure, and patient condition. Variations in study design, data collection methods, and perspectives (nurses vs. patients) contributed to inconsistent findings across studies. Conclusion Nurse workload significantly influences response time in emergency settings. However, this relationship is affected by multiple interacting factors such as work environment, professional competency, and support systems. It is recommended to implement real-time workload assessment tools, enhance training programs, and conduct mixed-method studies that differentiate physical, mental, and emotional workload dimensions to improve emergency response performance and patient safety.